(untitled) (ENTHYMEMA, 2023)
If the early Web had allowed literary authors to freely assume different forms (anonymous, collective, pseudonymous), today the advent of social networks and Web 2.0 impose the construction of a virtual literary posture as close as possible to the real one. The aim here is to analyse, starting with Instagram, the literary posture of Édouard Louis and Jonathan Bazzi, whose works are extremely similar in theme and form. The analysis will attempt to understand how social networks intervene in the process of the construction of the literary posture and if, starting from them, a new understanding can be achieved.